Manajemen Pendidikan dalam Meningkatkan Kualitas Peserta Didik di SD Islam Puspa Bangsa Banyuwangi - Agus Wijaksono; Mushoffa Mushoffa (Jurnal Pendidikan Indonesia (JOUPI), 2023)
National education management in Indonesia as a whole still remains to be centralized, so that less encouraging democratization and decentralization of education. Basically, education management issues concerning the efficiency in the utilization of existing resources National education management is a neat strategy to overcome the negative effects of globalization. Hence strengthening it will steer globalization in a positive direction for the development of the nation. Centralized management system of education that has been proven to not bring significant progress to improve the quality of education in general. Even in certain cases, the centralized management of education had led to limit creativity in various types and levels of education.